An Investigation of the Effects of Workplace Friendship, Trust Climate and Psychological Capital on Individual Knowledge Sharing Behaviour - Yang, Jingchen (2020)
Knowledge plays a significant role on contemporary management and economics. How to promote individuals to share and interact knowledge with others in organisations decide what level of knowledge could affect. This research draw from antecedents of knowledge sharing behaviour, expand what will affect knowledge sharing behaviour by using a moderated mediation model. In order to test the moderated mediation model, 301 available data were used by analysing with SPSS, Mplus and R. Results demonstrate that workplace friendship is positively associated with knowledge sharing behaviour through a mediation named psychological capital (PsyCap). Specifically, a good relationship in workplace could promote psychological capital and could increase knowledge sharing behaviour. Furthermore, trust climate positively moderate the relationship between workplace friendship and then impact on promoting knowledge sharing behaviour. In other words, high trust climate could develop workplace friendship and PsyCap more easily due to colleagues trust with each other are more willing to share knowledge. This research highlights the function of PsyCap which did not received enough attentions in prior research. Theoretical and practice discussion are included at the end of this dissertation.